2021
DOI: 10.18502/ijph.v50i8.6817
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mitochondrial DNA Copy Number and Oxidative Damage in Patients with Hashimoto’s Thyroiditis

Abstract: Background: The purpose of present study was to investigate mitochondrial DNA copy number (mtDNAcn) and mtDNA damage in peripheral blood of patients with Hashimoto's thyroiditis (HT) and healthy controls (HC). Methods: The relative mtDNAcn and oxidative DNA damage in this case-control study were measured in peripheral blood of 50 patients with Hashimoto’s thyroiditis and 50 healthy controls using quantitative real-time PCR. The study was conducted in Tehran University of Medical Sciences hospital, Tehran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In the group of patients with subclinical hypothyroidism and HT, mean total oxidant status (TOS) and oxidative stress index (OSI) were significantly higher in individuals, who developed overt disorders, which raised the suspicion that oxidative stress may be an effective risk factor in the development of overt hypothyroidism in the course of HT [38]. According to already achieved data, mitochondrial DNA copy number (mtDNAcn) and mtDNA damage could be also perceived as other possible markers of OS in patients with HT [39,40]. It is worth mentioning here that microRNAs (miRNAs) are the small non-coding particles of RNA that regulate gene expression at the posttranscriptional level.…”
Section: Oxidative Stress In Thyroid Disordersmentioning
confidence: 99%
“…In the group of patients with subclinical hypothyroidism and HT, mean total oxidant status (TOS) and oxidative stress index (OSI) were significantly higher in individuals, who developed overt disorders, which raised the suspicion that oxidative stress may be an effective risk factor in the development of overt hypothyroidism in the course of HT [38]. According to already achieved data, mitochondrial DNA copy number (mtDNAcn) and mtDNA damage could be also perceived as other possible markers of OS in patients with HT [39,40]. It is worth mentioning here that microRNAs (miRNAs) are the small non-coding particles of RNA that regulate gene expression at the posttranscriptional level.…”
Section: Oxidative Stress In Thyroid Disordersmentioning
confidence: 99%
“…The role of oxidative stress has been shown in many autoimmune diseases such as systemic sclerosis, myasthenia gravis, dermatomyositis, vitiligo, and Hashimoto’s thyroiditis, among others [ 30 , 31 , 32 , 33 , 34 ]. In a recent study, the levels of ROS in peripheral blood neutrophils of patients with rheumatoid arthritis (RA) were evaluated, which, in addition to being elevated, were associated with the severity of the disease [ 35 ].…”
Section: Regulatory T Cells and Diseasementioning
confidence: 99%
“…However, it should be noted that the majority of those studies were conducted in Asian populations. One study indicated significantly higher mitochondrial DNA CN and mitochondrial oxidative damage in HT patients [17]. To date, mtDNA variations have not been investigated in terms of PCOS and HT comorbidity.…”
Section: Introductionmentioning
confidence: 99%